Single-board-computer-based traffic generator for a heterogeneous and hybrid smart grid communication network - Quang D.N.; See O.H.; Chee L.L.; Xuen C.Y.; Karuppiah S.A.L. (Maxwell Science Publications, 2023)
In smart grid communication implementation, network traffic pattern is one of the main factors that affect the system's performance. Examining different traffic patterns in smart grid is therefore crucial when analyzing the network performance. Due to the heterogeneous and hybrid nature of smart grid, the type of traffic distribution in the network is still unknown. The traffic that popularly used for simulation and analysis no longer reflects the real traffic in a multi-technology and bi-directional communication system. Hence, in this study, a single-board computer is implemented as a traffic generator which can generate network traffic similar to those generated by various applications in the fully operational smart grid. By placing in a strategic and appropriate position, a collection of traffic generators allow network administrators to investigate and test the effect of heavy traffic on performance of smart grid communication system. © Maxwell Scientific Organization, 2014.